How Parenting Styles Link Career Decision-Making Difficulties in Chinese College Students? The Mediating Effects of Core Self-Evaluation and Career Calling - Tian, Xiaoyan; Huang, Bijuan; Li, Hongxia; Xie, Shaowen; Afzal, Komal; Si, Jiwei; Hu, Dongmei (Frontiers in Psychology, 2021)
The purpose of this study was to explore the relationship between parenting styles and career decision-making difficulties in college students, and uncovered the mediating roles of core self-evaluation and career calling. A total of 1127 undergraduates were recruited to complete the questionnaires about parenting styles, core self-evaluation, career calling, and career decision-making difficulties. The results showed that: (1) Positive and negative parenting styles could positively predict career decision-making difficulties in college students; (2) Core self-evaluation and career calling mediated the relationship between parenting styles and career decision-making difficulties. Sequential dual mediators only found in which positive paternal and maternal parenting styles predict career decision-making difficulties through core self-evaluation and career calling; (3) Further analysis revealed gender difference in the relationship between parenting styles and career decision-making difficulties. The relation between paternal positive parenting style and career decision-making difficulties was significant in male students, but absent in female students; the relation between maternal positive parenting and career decision-making difficulties and the relation between paternal negative parenting and career calling were significant in female students, but absent in male students; and the relation between career calling and career decision-making difficulties was greater in male than in female. The current study expanded and deepened those existing understandings about the relationship between parenting styles and adolescents’ career decisions, so as to further reveal its internal mechanism and provide more reasonable suggestions and targeted guidance for career counseling.